Further research problems and theorems on prime power groups - Berkovich, Yakov G. (Array, 2019)
Below we state a great number of research problems concerning finite p-groups. This list is a continuation of the six lists in [1, 2, 3, 4, 5, 6]. Below we also stated some new theorems with proofs. For explanation of notation see the beginning of the above volumes.